TRANSFORMING VOCATIONAL EDUCATION THROUGH ARTIFICIAL INTELLIGENCE: COMPETENCY DEVELOPMENT FOR THE DIGITAL ECONOMY - Jalilova Muxtasar Karimjonovna; Rahmatullayeva Umida Mahamadjon qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract Artificial  Intelligence  (AI)  technologies  are  rapidly  transforming  vocational education systems worldwide by enabling the development of competency-based skills aligned  with the digital economy.  This  study  explores  the  integration  of  AI-driven adaptive learning systems in Uzbek technical schools and colleges, focusing on their pedagogical effectiveness and practical outcomes. The findings demonstrate that AI-supported  learning  environments  significantly  improve  students’  technical  and cognitive competencies, promote personalized learning experiences, and enhance their readiness  for  the  evolving  labor  market.  The  research  highlights  the  strategic importance of AI in modernizing vocational education and fostering a competitive, digitally skilled workforce.